Meet Diego! - Valdes, Leslie; Illustrated by Hall, Susan (London Simon & Schuster, 2005)
Meet Diego, Dora's cousin, when Dora and Boots visit all the animals that Diego rescues. Dora's cool cousin, Diego, loves animals and helps to rescue them when they are in danger. But when Baby Jaguar cries for help, can Diego rescue him before he plunges into the waterfall? Find out with Dora, Boots and Diego in this adventure.
Include Colour Illustrations
Keywords: Dora, the Explorer (Fictitious character)